THE EVALUATION CRITERIA OF IELTS READING AND LISTENING - Aliyeva Nuray Vasif (Scientific Research and Experimental Development, 2024)
This paper critically evaluates the assessment procedures employed in the International English Language Testing System (IELTS) listening and reading sections. Drawing upon established literature and empirical evidence, the examination centers on the validity, reliability, and effectiveness of these assessment components in gauging candidates' English language proficiency. Through an exploration of the structural intricacies, scoring methodologies, and research findings, this paper provides a nuanced understanding of the evaluation mechanisms inherent in the IELTS listening and reading sections, offering insights for both test administrators and candidates